Rookery - Brimhall, Traci, 1982- (Book collections on Project MUSE., 2010)
Traveling to the most intimate extremes of the human heart Fraught with madness, brutality, and ecstasy, Traci Brimhall's Rookery delves into the darkest and most remote corners of the human experience. From the graveyards and battlefields of the Civil War to the ancient forests of Brazil, from desire to despair, landscapes both literal and emotional are traversed in this unforgettable collection of poems. Brimhall guides readers through ever-winding mazes of heartbreak and treachery, and the euphoric dreams of missionaries. The end of days, the intoxication of.